Emphatic Language in Instagram - Alfina Gustiany Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to find out the components of empathy contained in Instagram. Problems with two components and four aspects of empathy contained in Instagram account comments. The theory used is Davis' emphaty theory, namely 2 components of empathy, the first is the affective component which has two aspects, namely empathic concern and personal distress. The second is the cognitive component, namely perspective taking and fantasy empathy. The data was collected through the Instagram comments of the @ataliapr account. The method used is descriptive qualitative. This study concludes that there are two components that are most widely used, namely the affective component, empathic concern by 42% and personal distress by 39%. Then followed by the cognitive component, namely perspective taking by 13% and fantasy empathy by 6%. This is because the caption on @ataliapr's post touches the hearts of the readers.